STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBUDAYAKAN KEDISPLINAN - Hidayah, Nurul; Wijaya, Arinda Oktanthia; Puteri, Nazarni Dara; Murhartoyo; Ilmi, Zurjani; Suriansyah; Purwanti, Ratna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Discipline is one of the fundamental aspects in creating a school culture that is conducive to the learning process. This article examines the role of school principals in cultivating discipline within the school environment. The study employs a qualitative approach through literature review and analysis of educational leadership practices. The findings reveal that the principal of SMKN 2 Pelaihari acts as a role model, motivator, and supervisor in instilling the values of discipline among teachers, staff, and students. The strategies implemented include establishing clear regulations, maintaining consistency in enforcing school rules, providing motivation, and fostering a collaborative culture oriented toward disciplinary values. Furthermore, effective leadership is able to build harmonious communication and create a school environment that supports the internalization of discipline as part of students’ character development. In conclusion, the leadership of the school principal is a key factor in shaping a sustainable culture of discipline, which positively impacts the quality of learning and the overall school climate.